Management of technical projects MGMT 6810 (John Wiley & Son, 2001)
Based on the extensive and diverse project management experience within Fortune 500 companies and U.S. government agencies, the authors provide a practical and highly informative guide that can be applied easily to a variety of technical projects, regardless of industry! Revised and updated to reflect today's revolutionary changes and extraordinary business challenges, the book provides proven, practical management strategies to give your projects and your teams the competitive advantage